2013
DOI: 10.9738/intsurg-d-12-00015.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Recurrence-Free Survival After Metachronous Surgery of the Stomach and Liver for Gastric Adenocarcinoma and Multiple, Synchronous Liver Metastases: A Case Report and Review of Literature

Abstract: This report describes a 58-year-old woman with gastric adenocarcinoma and liver metastases, who survives for more than 18 years after diagnosis. At diagnosis and first surgery, a moderately differentiated gastric adenocarcinoma with subserosal invasion was detected, along with 2 regional lymph node metastases and 2 liver metastases. She underwent gastrectomy and regional lymph node dissection but did not undergo liver operation then. After gastrectomy, she received adjuvant chemotherapy for 1 month but discont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The 5ySR of patients with LMGC in our study is much lower than that observed in previous studies examining LMGC patients from Beijing or Japan (9.2%, 12.2%, and 31.1%, respectively) (25,26). Several reports, including ours, have demonstrated that old age, Lauren classification, submucosal invasion, vascular involvement, lymph node metastasis, tumour differentiation, the number of LMs, and tumour size are significant factors influencing the prognosis of patients with LMGC (27)(28)(29)(30). In the present study, we also identified POCT and palliative chemotherapy as independent prognostic factors for patients with LMGC.…”
Section: Discussionsupporting
confidence: 76%
“…The 5ySR of patients with LMGC in our study is much lower than that observed in previous studies examining LMGC patients from Beijing or Japan (9.2%, 12.2%, and 31.1%, respectively) (25,26). Several reports, including ours, have demonstrated that old age, Lauren classification, submucosal invasion, vascular involvement, lymph node metastasis, tumour differentiation, the number of LMs, and tumour size are significant factors influencing the prognosis of patients with LMGC (27)(28)(29)(30). In the present study, we also identified POCT and palliative chemotherapy as independent prognostic factors for patients with LMGC.…”
Section: Discussionsupporting
confidence: 76%
“…Current studies suggest that lymph node metastasis, differentiation, size and the number of liver metastases may be the main factors influencing the prognosis of patients with LMGC. 17 , 18 Liu et al retrospectively analyzed the clinicopathological data of 37 patients with LMGC who underwent surgical resection, and found a 5-year survival rate reaching 50% in patients without lymph node metastasis, which was significantly better than those with lymph node metastasis. 19 The degree of liver metastasis determines whether R0 resection could be obtained after surgery, thereby constituting the main prognostic factor in LMGC.…”
Section: Discussionmentioning
confidence: 99%